Directions and methods of improving the career development of the public servants of the federal ministries - K. M. Bekmurzieva (Вестник университета)
The current issues of the organization of the effective civil service of the Russian Federation have been considered. Factors and circumstances, affecting the career process of a civil servant of the Federal Ministry, have been determined. The necessity of improving the method of assigning a class rank to the civil servant of the Federal Ministry has been substantiated. The conditions and processes of career growth of civil servants of the Federal Ministries have been analyzed. Foreign experience in сareer advancement of civil servants has been considered. Arguments, justifying the need to improve the career forms of civil servants of the Federal ministries, have been presented.